Biogenic tellurium nanorods as a novel antivirulence agent inhibiting pyoverdine production in Pseudomonas aeruginosa - Mohanty, Anee (2013)
While antibiotic resistance in bacteria is rapidly increasing, the development of new antibiotics has decreased in recent years. Antivirulence drugs disarming rather than killing pathogens have been proposed to alleviate the problem of resistance inherent to existing biocidal antibiotics. Here, we report a nontoxic biogenic nanomaterial as a novel antivirulence agent to combat bacterial infections caused by Pseudomonas aeruginosa. We synthesized, in an environmentally benign fashion, tellurium nanorods (TeNRs) using the metal-reducing bacterium Shewanella oneidensis, and found that the biogenic TeNRs could effectively inhibit the production of pyoverdine, one of the most important virulence factors in P. aeruginosa. Our results suggest that amyloids and extracellular polysaccharides Pel and Psl are not involved in the interactions between P. aeruginosa and the biogenic TeNRs, while flagellar movement plays an important role in the cell-TeNRs interaction. We further showed that the TeNRs (up to 100 µg/ml) did not exhibit cytotoxicity to human bronchial epithelial cells and murine macrophages. Thus, biogenic TeNRs hold promise as a novel antivirulence agent against P. aeruginosa.